Per leggere la società - Bettin Lattes, Gianfranco (Studi e saggi, 2003)
The book is a successful research experiment that has also been successful as a teaching resource. It proposes a critical evaluation of the conceptual tools developed to read and understand a society. Ten sociological concepts are addressed (Community, Citisenship, Social Class, Social Capital, Gender, Executive Class, Political Party, Political Culture, Subculture, Antipolitics) each examined by a young researcher active in the Florentine doctorate of Sociology and Political sociology. An involvement of young people that has allowed a reinterpretation of "old" concepts and the identification of the heuristic effectiveness of "new" concepts.